Micromechanics-based constitutive model and its application to lattice analysis of plain concrete - Li, Qingliu. (2008)
The main purpose of this research is to develop a micromechanical constitutive model for concrete, which is able to explain the relationship between the macropic characteristics and the microstructure of brittle composite material such as concrete.